Improved insulin sensitivity associated with reduced mitochondrial complex IV assembly and activity. Issue 4 (14th December 2012) - Deepa, Sathyaseelan S.; Pulliam, Daniel; Hill, Shauna; Shi, Yun; Walsh, Michael E.; Salmon, Adam; Sloane, Lauren; Zhang, Ning; Zeviani, Massimo; Viscomi, Carlo; Musi, Nicolas; Van Remmen, Holly
Abstract : Mice lacking Surf1, a complex IV assembly protein, have 50‐70% reduction in cytochrome c oxidase activity in all tissues yet a paradoxical increase in lifespan. Here we report that Surf1 –/– mice have lower body (15%) and fat (20%) mass, in association with reduced lipid storage, smaller adipocytes, and elevated indicators of fatty acid oxidation in white adipose tissue (WAT) compared with control mice. The respiratory quotient in the Surf1 –/– mice was significantly lower than in the control animals (0.83–0.93 vs. 0.90–0.98), consistent with enhanced fat utilization in Surf1 –/– mice. Elevated fat utilization was associated with increased insulin sensitivity measured as insulin‐stimulated glucose uptake, as well as an increase in insulin receptor levels ( 2‐fold) and glucose transporter type 4 (GLUT4; 1.3‐fold) levels in WAT in the Surf1 –/– mice. The expression of peroxisome proliferator‐activated receptor γ‐coactivator 1‐α (PGC‐1α) mRNA and protein was up‐regulated by 2.5‐ and 1.9‐fold, respectively, in WAT from Surf1 –/– mice, and the expression of PGC‐1α target genes and markers of mitochondrial biogenesis was elevated. Together, these findings point to a novel and unexpected link between reduced mitochondrial complex IV activity, enhanced insulin sensitivity, and increased mitochondrial biogenesis that may contribute to the increased longevity in the Surf1 –/– mice.—Deepa, S. S., Pulliam, D., Hill, S., Shi, Y., Walsh, M. E., Salmon, A., Sloane, L., Zhang, N., Zeviani, M., Viscomi, C., Musi, N., Van Remmen, H. Improved insulin sensitivity associated with reduced mitochondrial complex IV assembly and activity. FASEB J. 27, 1371–1380 (2013). www.fasebj.org